Enduring drought: effects and strategies for Brassica crop resilience - Asha Rani Sheoran; Nita Lakra; Baljeet Singh Saharan; Annu Luhach; Neelam Kumari Mandal; Chandra Shekhar Seth; Deepansh Sharma; Anita Rani Santal; Surekha; Pardeep Kumar Sadh; Vishnu Dayal Rajput; Joginder Singh Duhan (Academia Biology)
Brassica crops, encompassing vital vegetables like broccoli, cauliflower, cabbage, and oilseed crops such as mustard and rapeseed, encounter significant challenges when confronted with drought stress. Drought stress induces various intriguing physiological changes, including reduced water uptake, stomatal closure, decreased photosynthesis, and disruptions in osmotic balance, directly impacting growth, yield, and produce quality. Additionally, the stress brought on by drought increases the buildup of reactive oxygen species (ROS), lipid peroxidation and disrupts antioxidant defense mechanisms. These alterations result in oxidative stress and cellular damage. In response, plants tend to accumulate osmoprotectants, antioxidants, and drought-responsive proteins. At molecular level, researchers have identified specific genes and regulatory networks activated in retaliation to drought stress in Brassica crops, significantly advancing our understanding of their drought adaptation mechanisms. This review sheds light on the intricate effects of drought stress on Brassica crops, revealing their physiological, biochemical, and molecular responses and some key management strategies. By comprehending these mechanisms, we gain valuable insights into how Brassica crops adapt to drought conditions. With this knowledge, researchers and breeders can enhance drought tolerance in Brassica crops, ensuring food security and promoting sustainable agriculture in water-scarce regions. Embracing these discoveries promises a more resilient and productive agricultural future.